2011
DOI: 10.1097/brs.0b013e3181dce34c
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Stem Cell Therapy Maintains Vertebral Blood Flow and Contrast Diffusion Through the Endplate in Experimental Intervertebral Disc Degeneration

Abstract: Stem cell and hydrogel therapy is able to partly regenerate IDD and maintain perfusion and permeability of the vertebral endplate and subchondral bone. Dynamic contrast-enhanced MRI may become an important tool in future investigation of the vertebral endplate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 39 publications
0
25
0
2
Order By: Relevance
“…Thirty-seven of the animal studies reviewed utilized stem cells. Among these, 10 studies used autologous stem cells,(2736) 15 studies used allogeneic cells,(25, 3750) and 12 used xenogeneic cells (23, 5161) (Table 1). Studies involving allogeneic and xenogeneic cells have shown good survival of these cells in the IVD, confirming that the disc niche is a relatively immunologically privileged site.…”
Section: Cell Sources and Typesmentioning
confidence: 99%
“…Thirty-seven of the animal studies reviewed utilized stem cells. Among these, 10 studies used autologous stem cells,(2736) 15 studies used allogeneic cells,(25, 3750) and 12 used xenogeneic cells (23, 5161) (Table 1). Studies involving allogeneic and xenogeneic cells have shown good survival of these cells in the IVD, confirming that the disc niche is a relatively immunologically privileged site.…”
Section: Cell Sources and Typesmentioning
confidence: 99%
“…Apart from drug administration, this route is used for investigating nutrient pathways by following the movement of intravenously injected gadolinium in the disc by MRI (Bendsten et al, 2011;Nguyen-minh et al, 1998;Rajasekaran et al, 2004Rajasekaran et al, , 2008. While intradiscal injection of bioactive agents such as growth factors is currently the preferred route for experimental studies of disc repair (Bae and Masuda, 2011;Woods et al, 2011), an increasing number of studies suggests that needle puncture of the annulus may lead to disc degeneration and increases in the risk of herniation and of post injection surgery (Carragee et al, 2009;Michalek et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…One disc was stabbed with a no. 23 scalpel at the left anterolateral part at a depth of 6 mm (just reaching the NP; in a pilot study, we measured the AF width to be about 6 mm) as a positive control [15,16]. In the other disc, a slice defect was created in the vertebral body both caudally and cranially to the disc by drilling and curetting.…”
Section: Surgical Proceduresmentioning
confidence: 99%